Functional analysis of amino acid residues encompassing and surrounding two neighboring H-2Db-restricted cytotoxic T-lymphocyte epitopes in simian virus 40 tumor antigen. - Lippolis, J D (1995)
Simian virus 40 tumor (T) antigen contains three H-2Db-and one H-2Kb-restricted cytotoxic T lymphocyte (CTL) epitopes (sites). Two of the H-2Db-restricted CTL epitopes, I and II/III, are separated by 7 amino acids in the amino-terminal one third of T antigen. In this study, we determine if the amino acids separating these two H-2Db-restricted CTL epitopes are dispensable for efficient processing and presentation. In addition, the importance of amino acid residues lying within and flanking the H-2Db-restricted epitopes I and II/III for efficient processing, presentation, and recognition by site-specific CTL clones was determined by using T-antigen mutants containing single-amino-acid substitutions between residues 200 and 239. Using synthetic peptides in CTL lysis and major histocompatibility complex class I stabilization assays, CTL recognition site I has been redefined to include residues 206 to 215. Substitutions in amino acids flanking either site I or site II/III did not affect recognition by any of the T-antigen-specific CTL clones. Additionally, the removal of the 7 residues separating site I and site II/III did not affect CTL recognition, thus demonstrating that these two epitopes when arranged in tandem in the native T antigen can be efficiently processed and presented to CTL clones. Differences in fine specificities of two CTL clones which recognize the same epitope (Y-1 and K-11 for site I and Y-2 and Y-3 for site II/III) have been used in conjunction with synthetic peptide variants to assign roles for residues within epitopes I and II/III with respect to TCR recognition and/or peptide-major histocompatibility complex association.